Atmospheric pressure plasma synthesis of adaptable coatings based on castor oil urethane dimethacrylate and their properties - Eusebiu-Rosini Ionita; Maria-Daniela Ionita; Antoniu Moldovan; Cristina Surdu-Bob; Violeta Melinte; Andreea L. Chibac-Scutaru; Andrada Lazea-Stoyanova (Applied Surface Science Advances)
Urethane-dimethacrylate polymers are generated using light energy, in the presence of photoinitiators, and are the choice materials for many composite materials, biomaterials, optical materials or coatings. In this study, we present an alternative, new, synthesis method for castor oil polymethacrylate (CO-PMA) films by exposure of a liquid precursor (namely castor oil urethane dimethacrylate (CO-UDMA)) to a non-thermal atmospheric pressure cylindrical plasma source. This is a photoinitiator free process, an open-air atmosphere technique and uses a single plasma polymerization step. We have obtained polymeric layers in two modes, in stationary or dynamic plasma exposure mode. The experimental results show that our plasma method is suitable to generate compact polymeric layers, with no trapped unpolymerized precursor, showing a bumpy or microscale ripples surface appearance. However, the surface and cross-section analyses indicate that the dynamic layer has a nanometric flat surface, a more pronounced hydrophobic character and is thicker. In short, our plasma-based method for generation of CO-PMA layers, in dynamic mode, does not require toxic photoinitiators, is simple, can be applied to temperature-sensitive materials and is scalable to large areas.